2012
DOI: 10.3892/ijmm.2012.976
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of genetic variants of APOA5 and BTN2A1 on dyslipidemia or metabolic syndrome

Abstract: Abstract. We previously showed that the -1131T→C polymorphism (rs662799) of the apolipoprotein A-V gene (APOA5) and the C→T polymorphism (rs6929846) of the butyrophilin, subfamily 2, member A1 gene (BTN2A1) were significantly associated with an increased serum concentration of triglycerides, a decreased serum concentration of high density lipoprotein (HDL)-cholesterol, and the prevalence of metabolic syndrome (MetS) in Japanese individuals. The purpose of the present study was to examine whether these polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In accordance with our analysis, Wu et al reported that APOA5 rs662799 had a positive interaction with environmental factors, such as tobacco use and alcohol consumption, on MetS with participations in China32. Likewise, a previous study by Hiramatsu et al found the synergistic effects of APOA5 rs662799 and the rs6929846 SNP of the butyrophilin subfamily 2 member A1 ( BTN2A1 ) gene on the development of MetS in Japanese individuals33. Son et al also suggested an interaction between APOA5 rs662799 and alcohol drinking as well as an interaction between APOA5 rs662799 and physical activity in affecting triglyceride levels in Korean men, but no interaction between APOA5 rs662799 and smoking status34.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with our analysis, Wu et al reported that APOA5 rs662799 had a positive interaction with environmental factors, such as tobacco use and alcohol consumption, on MetS with participations in China32. Likewise, a previous study by Hiramatsu et al found the synergistic effects of APOA5 rs662799 and the rs6929846 SNP of the butyrophilin subfamily 2 member A1 ( BTN2A1 ) gene on the development of MetS in Japanese individuals33. Son et al also suggested an interaction between APOA5 rs662799 and alcohol drinking as well as an interaction between APOA5 rs662799 and physical activity in affecting triglyceride levels in Korean men, but no interaction between APOA5 rs662799 and smoking status34.…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of constructed haplotypes with SNPs in MTHFR, APOA5 and APOC3 genes, showed a highly significant association between one haplotype and MS in the Greek Population [ 43 ]. Gene-gene interaction suggested that polymorphisms in APOA5 and BTN2A1 genes may have synergistic effects on the development of MS in Japanese individuals [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“… 31 This might be from synergistic effects of genetic variants of ITPKC and CASP3 , which could be observed in other diseases. 32 33 Based on these results, administration of cyclosporine A for the treatment of IVIG-resistant KD patients is theoretically feasible, because cyclosporine A suppresses activation of NFAT. Currently, cyclosporine A is already being used 34 in treatment and further research projects are ongoing.…”
Section: Genetic Susceptibility Related To Kdmentioning
confidence: 99%